Obscuring Labor Exploitation with Abstracted Data and Liberal Apologism - Oplas, Bienvenido S. (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of the book The Sugar Workers: Two Studies by the Institute of Labor and Manpower Studies, Ministry of Labor and Employment.